Medieval Mystical Sources And Methodological Basis Of Studying Family Heritage In Modern Research (Zien Journal of Social Sciences and Humanities, 2024)
In this article, the legacy of the mystic scholar Sahl ibn Abdullah Tustari was comparatively studied and the differences between the information presented in the medieval sources and modern researches were highlighted.